Coaching livestock and fish projects on gender: Experiences from distance and field participation - Sultana, N. (International Livestock Research Institute, 2016)
Nasrin Sultana acted as a coach for the Livestock Feed Assessment Tool, or FEAST. This meant integrating gender in a tool that was already heavily used. It was necessary to integrate gender without making the tool too heavy, which would risk it losing its popularity. She also coached the feed value-chain assessment study in Bangladesh. A key learning was the need to focus on ownership in the project and to foster communication between technical and gender specialists. It is a challenge to work on technical issues and at the same time integrate gender in a proper way. It has been a shared learning for everyone involved. Interview with Nasrin Sultana (Royal Tropical Institute) for the book "A different kettle of fish? Gender integration in livestock and fish research". http://hdl.handle.net/10568/76684